Differential Impact of Salinity Stress on Seeds Minerals, Storage Proteins, Fatty Acids, and Squalene Composition of New Quinoa Genotype, Grown in Hyper-Arid Desert Environments - Toderich, Kristina N.; Mamadrahimov, Azimjon A.; Khaitov, Botir B.; Karimov, Aziz A.; Soliev, Azamjon A.; Nanduri, Kameswara Rao; Shuyskaya, Elena V. (Frontiers in Plant Science, 2020)
The effects of climate change and soil salinization on dryland ecosystems are already widespread, and ensuring food security is a crucial challenge. In this paper we demonstrate changes in growth performance and seed quality of a new high-yielding quinoa genotype (Q5) exposed to sodium chloride (NaCl), sodium sulfate (Na2SO4), and mixed salts (NaCl+ Na2SO4). Differential responses to salt stress in growth performance, seed yield and seed quality were identified. High salinity (mixed Na2SO4 + NaCl) reduces plant height by ~30%, shoot and root dry weights by ~29%, head panicle length and panicle weight by 36-43%, and seed yield by 37%, compared with control conditions. However, the 1000-seed weight changes insignificantly under salinity. High content of essential minerals, such as Fe, Zn, and Ca in quinoa Q5 seeds produced under salinity gives the Q5 genotype a remarkable advantage for human consumption. Biomarkers detected in our studies show that the content of most essential amino acids is unchanged under salinity. The content of amino acids Pro, Gly, and Ile positively correlates with Na+ concentration in soil and seeds , while the content of squalene and most fatty acids negatively correlates .. Variation in squalene content under increasing salinity is most likely due to toxic effects of sodium and chlorine ions as a result of the decrease in membrane permeability for ion movement as a protective reaction to an increase in the sodium ion concentration. Low squalene accumulation might also occur to redirect the NADPH cofactor to enhance the biosynthesis of proline in response to salinity, as both syntheses (squalene and proline) require NADPH. This evidence can potentially be used by the food and pharmaceutical industries in the development of new food and health products.